In vitro bactericidal efficacy of a new triple antibiotic paste formulation against Enterococcus faecalis biofilm - Smittiset B. (2023)
The aim of this study was to evaluate the bactericidal efficacy on Enterococcus faecalis biofilm of a novel, low-concentration triple-antibiotic paste (TAP-L2) in propylene glycol/carboxymethylcellulose vehicle (VEH-2), a ready-to-use prototype, compared with two currently used products; a low-concentration (TAP-L1) and a high-concentration paste (TAP-H1) mixed in macrogol/propylene glycol vehicle (VEH-1). Sixty-two root canals were infected with E. faecalis biofilm, medicated with (a) TAP-L1, (b) TAP-L2, (c) TAP-H1, (d) VEH-1 or (e) VEH-2 (n = 10) and incubated for 21 days. Live/dead assays were performed using confocal laser scanning microscopy (CLSM), and dead bacteria (%) were calculated. The TAP-H1 group demonstrated the highest dead bacteria (67.54 ± 2.38%), which was significantly higher than the TAP-L2 and TAP-L1 groups (56.85 ± 7.11% and 54.23 ± 10.19%) (p < 0.05). The TAP groups demonstrated significantly higher dead bacteria than the VEH-1 and VEH-2 groups (47.51 ± 6.41% and 45.14 ± 8.28%) (p < 0.05). The ready-to-use TAP-L2 had antibacterial activity comparable to TAP-L1, both of which were lower than TAP-H1.